Using textual statistics to support competitiveness company analysis - Filipczyk, Anna (Zastosowanie statystycznej analizy tekstu do wspomagania analizy konkurencyjności firmy, 2011)
Knowledge of the internal and external activity aspects of an enterprise is its essential resource. Companies communicate on-line with others through their own websites, which allows for easier identification of a company and finding new potential clients. Knowledge of business opponents gives a company the opportunity to follow market trends and to compete with other enterprises. Additionally, it may verify the attractiveness of its products and services in relation to businesses competing in a similar market by analysing various websites. To make this review faster and more automatic, a company can use an application based on the statistical text analysis method, which gives an opportunity to detect similarities between websites and therefore contributes to their competitiveness and company competitiveness in general
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 202, s. 22-29
Keywords: knowledge; Internet; semantic analysis; text; website